2018
DOI: 10.1016/j.pec.2018.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a brief faculty training to improve patient-centered communication while using electronic health records

Abstract: Faculty training on patient-centered EHR skills can enhance patient-doctor communication and promotes positive role modeling of these skills to learners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
(9 reference statements)
1
9
0
Order By: Relevance
“…29 Experts in promoting patient-centered use of the EHR advise that practitioners should educate their patients about the EHR by discussing its potential benefits and explaining how computers and the EHR aid in providing medical care. 17,18 In the present study, practitioners less frequently reported discussing these positive aspects of the EHR with their patients. In addition, fewer practitioners than patients agreed that the computer improved patients' understanding of their health (67.0% vs 76.8%), and approximately 50% of practitioners disagreed that computer use during a patient encounter added anything positive.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…29 Experts in promoting patient-centered use of the EHR advise that practitioners should educate their patients about the EHR by discussing its potential benefits and explaining how computers and the EHR aid in providing medical care. 17,18 In the present study, practitioners less frequently reported discussing these positive aspects of the EHR with their patients. In addition, fewer practitioners than patients agreed that the computer improved patients' understanding of their health (67.0% vs 76.8%), and approximately 50% of practitioners disagreed that computer use during a patient encounter added anything positive.…”
Section: Discussionmentioning
confidence: 58%
“…15 Experts have suggested that practitioners can mitigate the potentially negative effects of EHR use during clinical encounters by learning and using EHR-specific communication skills. 4,11,[16][17][18][19][20][21][22][23] To improve patient and practitioner experiences with the EHR, we sought to conduct an assessment of practitioner use of EHR communication skills, as well as patient and practitioner experiences and attitudes regarding EHR use during clinical encounters. In addition, we sought to determine whether suggested EHR-specific communication skills were associated with better patient and practitioner experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Further work is needed to understand how to tailor educational comics to different patient populations and clinical settings, such as the inpatient hospital environment, to effectively engage patients and physicians with the EHR. While this educational intervention targeted patients, it is also important to teach patient-centered EHR behaviors to physicians to promote patient-physician-EHR engagement [20][21][22][23][24][25][26]58,59], and these efforts should be pursued in tandem. Additionally, EHRs should evolve to account for user experience, patient health literacy levels, and language needs to help reduce the digital divide and health disparities [19,[60][61][62][63][64][65][66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…In a 2016 study on patient perceptions of physician EHR use in an academic primary care practice, patients were dissatisfied when physicians appeared more focused on the computer than on them and frustrated with lack of transparency and poor body positioning, which contributed to perceptions of decreased quality of care [7]. While best practices to promote patient-centered EHR use have been identified, most physicians and patients are unaware of these strategies to improve patient-physician-EHR communication [6,12,[20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…As educators develop communications curricula for patient-centered EHR use, these findings and other perspectives from diverse patients should inform the content [23,33,34]. Future efforts should investigate multilevel interventions to increase adoption of patient-centered EHR use strategies, including computer (EHR user interface or content), patient (activation or empowerment), environment (redesign or reposition equipment in rooms), and policy level (incentives) interventions.…”
Section: Discussionmentioning
confidence: 99%